Student’s Error in Writing Mathematical Problem Solving Associated With Corresponding Angles of The Similar Triangles - R H Parastuti; B Usodo; S Subanti (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
The research method used is descriptive qualitative.The aim of this research is to describe the student’s error in writing the resolution about the similarity of the two triangles. The student has many problems in mathematics include analyzing a triangle. A polygon that has three sides, three angles, and three cornersis called a triangle. The angle formed by the two sides of a triangle intersects with each other. The triangles are similar if the comparison lengths of the corresponding sides are same and the large of the corresponding angles are same. Three students are chosen as the subjects based on their score in the daily test about the similarity of two triangles. The students are given tests and then interviewed. Writing error by students in solving problems is analyzed based on Newman’s theory. The result obtained in this research is that error writing occurs because of the misconceptions when transforming the information from the problem. The students make mistakes in writing occurs when they have to solve the problems.